1998
DOI: 10.1016/s0886-3350(98)80196-x
|View full text |Cite
|
Sign up to set email alerts
|

Laser in situ keratomileusis assisted by corneal topography

Abstract: Preliminary results indicate that the concept of topographic-assisted LASIK is feasible. However, most eyes were undercorrected and had regression. One reason might be that corneal topography underestimated corneal irregularity, causing significant undercorrection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 18 publications
0
15
0
3
Order By: Relevance
“…Most published reports concern retreatment of decentred PRK patients using masking techniques or additional ablations [10]; results were generally unsatisfactory. Knorz and Jendritza [13] and Wiesinger-Jendritza et al [25] describe surgical management of corneal irregularities after LASIK treatments using a topographically guided laser. The results of topographically guided LASIK are promising but contact lenses might be of help until the efficacy of this treatment provides optimal visual performance.…”
Section: Discussionmentioning
confidence: 99%
“…Most published reports concern retreatment of decentred PRK patients using masking techniques or additional ablations [10]; results were generally unsatisfactory. Knorz and Jendritza [13] and Wiesinger-Jendritza et al [25] describe surgical management of corneal irregularities after LASIK treatments using a topographically guided laser. The results of topographically guided LASIK are promising but contact lenses might be of help until the efficacy of this treatment provides optimal visual performance.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible applications should be in surgeries that use intrastromal rings to correct refractive errors (20) , making it possible to determine more precisely how many diopters were corrected; and in topography assisted LASIK surgeries (7) .…”
Section: Discussionmentioning
confidence: 99%
“…It became clear that an instrument that could measure corneal surface would be even more efficient (6) . In a more recent study (7) it has been shown that LASIK procedures may be successfully assisted by preoperative corneal topography data. Although the authors did not use an Keywords: Corneal topography; Keratometry; Placido disc Videokeratograph (VKS) for monitoring corneal curvature during surgery intrasurgical device for these studies, we believe our system may be useful because preoperative data would be gathered with the patient in the position that the surgery would take place.…”
Section: Introductionmentioning
confidence: 99%
“…However, results thus far have been mixed. After encouraging initial clinical results 73 , one group treated 6 eyes with post-PRK/LASIK central islands using a topography-guided system. While patients with irregular corneal surfaces due to other reasons had significant improvements in topography and symptoms, they found the results to be sufficiently poor in the central island group to advise against using their technique in this patient population.…”
Section: Higher Order Aberrationsmentioning
confidence: 99%